THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND SELF-EFFICACY ON ENTREPRENEURIAL INTERESTS OF STUDENTS OF THE FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY - Prihastomo, Galih; Eryanto, Henry; Usman, Osly (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the effect of entrepreneurship education and self-efficacy on the entrepreneurial interest of economic students at the State University of Jakarta. The research method used in this research is quantitative. The population in this study found 410 students with a sample of 72 students. The variables of interest in entrepreneurship (Y), entrepreneurship education (X1), and self-efficacy (X2) are primary data using a Likert scale. The first data analysis technique used is the measurement of the external model consisting of individual reliability with results greater than 0.7 (> 0.7). Build reliability with results greater than 0.7 (>0.7). The composite value of reliability is greater than 0.7 (>0.7). The AVE value is greater than 0.5 (>0.5). Second, the measurement of the inner model which consists of r2 with 0.519. Then, the f-square of entrepreneurship education (X1) with a value of 0.189 and self-efficacy (X2) with a value of 0.483. Meanwhile, the VIF value is smaller than (5.00) so that there is no multicollinearity problem. Entrepreneurship Education coefficient value (X1) is 0.328 and t-statistic is 3.712>1.96 with p-value 0.00<0.05. The self-efficacy coefficient (X2) is 0.525 and the t-statistic is 6.601>1.96 with a p-value of 0.00<0.05.